The targeting nanothin polyelectrolyte shells in system with immobilized bacterial cells for antitumor factor production. Issue 8 (11th September 2013) - Granicka, L. H.; Borkowska, M.; Grzeczkowicz, A.; Stachowiak, R.; Szklarczyk, M.; Bielecki, J.; Strawski, M.
Abstract Development of anticancer treatment strategies is ongoing considering still inadequate efficiency of existing anticancer therapeutics. Moreover, the lack of therapeutic agents selectivity against the tumor cells requires further investigations into novel anticancer strategies. The use of pathogenic microorganisms producing an oncolytic agent may be an approach for apoptotic therapy in cancer treatment. The purpose of this study was to investigate the targeting efficiency of Bacillus subtilis bacterial cells coated with modified polyelectrolyte shells applied to protect the bacterial cells from potential host immune response as well as to enhance the tumor‐targeting efficiency. The shells were modified with transferrin to increase affinity toward the target tumor cells. The impact of bacterial cells coated with unmodified or modified nanothin shells on human leukemia cells was evaluated in vitro. It was observed that the bacterial cells coated with modified shells with incorporated transferrin exhibited stronger lethal impact on leukemia cells as compared to bacterial cells with unmodified shell coating. Applied modified membrane conformation allowing for functioning of encapsulated microorganisms may find potential use in local antitumor treatment purposes. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2662–2668, 2014.